A Systematic Review of Opportunities and Limitations of Innovative Practices in Sustainable Agriculture - Anita Boros; Eszter Szólik; Goshu Desalegn; Dávid Tőzsér (Agronomy)
A transformation is needed in agricultural production to satisfy the growing population-based increased food demands and overcome food safety challenges while supporting human health and the preservation of natural resources. Improving sustainable agricultural practices is essential for developing a long-term and resilient economy. This systematic review with meta-analyses aims to overview sustainable agriculture’s progress, trends, and future opportunities, focusing primarily on integrating novel technologies into recently prevailing agricultural operations. As a basis, an extensive literature search was conducted, identifying nearly 45,000 records related closely to various dimensions of sustainable agriculture. Out of these, based on a thorough selection process, 291 were included in further evaluations. The temporal distribution and content analyses indicated an improvement in the number of papers and the spectrum of addressed agricultural aspects. The analysis of the publications revealed that most traditional farming practices focus on mass food production and cannot deal with further interrelated sustainability challenges. On the other hand, sustainable agricultural practices consider sustainability’s environmental, economic, and social aspects, thereby preserving environmental health and supporting economic viability and social well-being. The integrative assessment in this study suggests that adopting novel, innovative practices can achieve the most significant progress toward agricultural sustainability. At the same time, a broad range of limitations and challenges are listed, which widely hinder the penetration of sustainability initiatives. To eliminate these barriers, consistent policy regulations are required, targeting specific agricultural problems, alongside a complex, education-based support system, further boosting initiatives related to the green transition in agriculture.